2003
DOI: 10.3201/eid0901.020265
|View full text |Cite
|
Sign up to set email alerts
|

Foot and Mouth Disease and Cryptosporidiosis: Possible Interaction between Two Emerging Infectious Diseases

Abstract: During 2001, a large outbreak of foot and mouth disease occurred in the United Kingdom, during which approximately 2,030 confirmed cases of the disease were reported, >6 million animals were slaughtered, and strict restrictions on access to the countryside were imposed. We report a dramatic decline in the reported incidence of human cryptosporidiosis in northwest England during weeks 13–38 in 2001, compared with the previous 11 years. This decline coincided with the period of foot and mouth restrictions. No si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 8 publications
0
23
1
Order By: Relevance
“…The significance of cattle in the zoonotic transmission of Cryptosporidium was previously shown in the United Kingdom during the 2001 foot-and-mouth disease outbreak. The animal contact restrictions put in place during that outbreak resulted in a significant reduction in the number of cases of human cryptosporidiosis caused by C. parvum (12).…”
Section: Discussionmentioning
confidence: 99%
“…The significance of cattle in the zoonotic transmission of Cryptosporidium was previously shown in the United Kingdom during the 2001 foot-and-mouth disease outbreak. The animal contact restrictions put in place during that outbreak resulted in a significant reduction in the number of cases of human cryptosporidiosis caused by C. parvum (12).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the predominance of C. parvum in a population has been considered the result of zoonotic transmission. Indeed, even in areas with a high percentage of infections due to C. parvum, massive slaughter of farm animals during foot-andmouth disease outbreaks can result in a reduction of the proportion of human infections due to C. parvum (10,28).…”
Section: Discussionmentioning
confidence: 99%
“…Long-term molecular surveillance has shown differences in the distribution of species by person, time and place in the UK (Anon, 2002;McLauchlin et al, 2000;Leoni et al, 2006, Nichols et al, 2006a) and the epidemiological "noise" is reduced when typing results are incorporated into routine surveillance, as is current in Scotland (Chalmers & Pollock, 2007). Changes in the epidemiology are more readily observed and investigated (Smerdon et al, 2003;Hunter et al, 2003;Sopwith et al, 2005). Analytical epidemiological studies have identified specific risk factors for sporadic cases: contact with farmed animals for C. parvum and travel abroad, changing nappies and contact with another infected person for C. hominis (Hunter et al, 2004a) and linked species to socio-economic factors is not clear (Glaberman et al, 2002), and it is important that this is underpinned by routine species identification to establish the background epidemiology.…”
Section: Th Emop August 2008mentioning
confidence: 99%